Parties and party systems: the experience of post-Soviet States (Journal of Philosophy Culture and Political Science, 2019)
This thesis was written in the framework of readings on April 2-3, 2019 of the international al-Farabi Forum "al-Farabi and modernity". The Forum had six sections and six discussion platforms. The fourth Discussion platform was entitled "Parties and party systems: the experience of post-Soviet States". The authors note that the States of the post-Soviet space after the collapse of the USSR went on various trajectories of transformation, including in the formation and development of party systems. As a result, three models of party systems and interaction between the President and Parliament were formed. At this discussion platform, the factors determining the formation and functioning of the party system were discussed. Strategies, role and performance of functions of important subjects of political process are analyzed.Keywords: party, party systems, political process, discussion platform, post-Soviet States.